Biorenewable rosin derived benzocyclobutene resin: a thermosetting material with good hydrophobicity and low dielectric constant. Issue 51 (20th September 2019) - Fu, Fei; Wang, Dan; Shen, Minggui; Shang, Shibin; Song, Zhanqian; Song, Jie
Abstract : The rosin structure was introduced into benzocyclobutene resin for the first time, and the thermosetting material with good hydrophobicity and low dielectric constant was prepared. Abstract : Development of bio-based polymers has been promoted by the growing concerns about the long-term sustainability and negative environmental footprint of petroleum-based polymer materials. A new monomer containing benzocyclobutene and allyl units has been developed by using rosin as the feedstock. The structure of the monomer was characterized by elemental analysis, MS, FT-IR and NMR spectroscopy. The monomer could be converted to the polymer via thermal ring-opening polymerization which was characterized via FT-IR, thermogravimetric analysis (TGA), atom force microscopy (AFM) and so on. The polymer showed good dielectric properties and hydrophobicity with an average dielectric constant of 2.51 in a range of frequencies from 0.1 to 18 MHz and a water contact angle of 106°. In addition, the polymer with other comprehensive performances exhibited a 5% weight loss temperature of 406 °C, a surface roughness ( R a ) of 0.658 nm in a 5.0 × 5.0 μm 2 area, hardness and Young's modulus of 0.283 and 3.542 GPa, and storage modulus of 11.46 GPa at 30 °C. These data suggest that the polymer may have potential application in electronics and microelectronics.